Teach For America's long arc: A critical race theory textual analysis of Wendy Kopp's works - Michael Barnes; Emily Germain; Angela Valenzuela (Arizona State University, 2016)
We read and analyzed 165,000 words and uncover a series of counter-stories buried within a textual corpus, authored by Teach For America (TFA) founder Wendy Kopp (Kopp, 1989, 2001; Kopp Farr, 2011), that offers insight into the forms of racism endemic to Teach For America. All three counter-stories align with a critical race theory (CRT) framework.  Specifically, we answer the following questions:  What evidence of institutional and epistemological racism is exposed by a CRT textual analysis of TFA's founding document and later works by Wendy Kopp?  To what extent has TFA appropriated the language of culturally relevant pedagogy, while advancing an uninterrogated neoliberal ideology? And, to what extent does TFA's contribution to a "culture of achievement" (Kopp Farr, 2011) constitute an actual "poverty of culture" (Ladson-Billings, 2006a) that enacts real harms on communities of color?